Análise da eficiência de corte de instrumentos de NiTi em movimento recíproco - Caroline Christine Santa Rosa (2014)
The cutting ability of endodontic instruments is complex and related to parameters such as cross-sectional geometry, cutting angles, pitch length, helical angle, metallurgical properties in addition to surface treatment. This study aimed to evaluate the cutting efficiency taking into account dimensional and geometric features of Reciproc - RC (VDW , Munich, Germany ) and WaveOne - WO ( Dentsply Maillefer , Ballaigues , Switzerland ), 25/.08 size instruments. Measurements of diameter at each millimeter from the tip, pitch length, helical angle, cross-sectional area and cutting angles were assessed. Samples of each system (n = 10) were photographed in a standardized manner using a Canon EOS 20D digital camera and image analysis was performed using ImagePro Plus 6.0 software. The cutting efficiency tests were carried out on a specific bench device by measuring the torque required during shaping of artificial canals. Ten instruments of each type were tested in prefabricated acrylic blocks containing an artificial canal previously explored with manual K-files. The motor was set at a speed of 300 rpm and torque 5 Ncm and the instruments were inserted into the canal at a constant speed of 0.09 mm/sec. In order to simulate the clinical condition, the shaping of the artificial canal was performed in two stages: initial instrument penetration through 13.5 mm, and then a second penetration until reach the full length, i.e., 16.5 mm. Statistical analysis was done with one-w y AN VA ( . ). A increase in diameter throughout the active part was observed in the two systems analyzed showing no statistically significant difference between RC and WO instruments (P = 0.521) in relation to the diameter at 3 mm from the tip (D3). The mean values of pitch lengths for RC were higher than those presented by WO instruments, although the difference was not statistically significant (P = 0.489). WO instruments had higher mean values of helical angles in comparison to RC instruments, but without statistically significant difference (P = 0.135). The cross section geometry as well as the area at 3 mm from the tip (A3) varied between the analyzed instruments. The RC samples showed slightly larger A3 mean value than WO instruments, but also without statistically significant difference (P = 0.521). The average of the two cutting angles on RC and WO instruments were similar. However, the five WO cutting angles were all significantly different when compared with each other. WO instruments in the first insertion depth and RC in the second stage of insertion required higher torque values respectively. The Reciproc and WaveOne instruments analyzed showed similar dimensional characteristics with RC presenting higher torque values in the second shaping stage.